Endogenous Growth: A Knife-Edge or the Razor's Edge? - Carl-Johan Dalgaard; Claus Thustrup Kreiner (University of Copenhagen, Economic Policy Research Unit (EPRU), 2002)
According to much of the recent growth literature the dramatic worldwide fertility decline currently taking place should ultimately lead to global economic stagnation. This pessimistic prediction is not shared by the original innovation-based growth literature. However, this strand of literature has in recent year been criticized for resting on implausible knife-edge assumptions and for being inconsistent with available evidence. In this paper, we argue that this conclusion is unwarranted.
Keywords: 330; Neue Wachstumstheorie